QUALITY OF LIFE IN CHRONIC PANCREATITIS WITH ACCOMPANYING ARTERIAL HYPERTENSION IN AGE ASPECT AND ITS RELATIONSHIP WITH MALNUTRITION MARKERS - Filippova, O.Yu.; Kryvoshey, V.V. (World of Medicine and Biology, 2023)
The problem of quality of life in chronic pancreatitis remains to be actual. The presence of comorbid pathology in chronic pancreatitis can be an aggravating factor for the quality of life and malnutrition manifestations. 110 patients were included. Standardized questionnaires were used (SF-36, GSRS). The levels of total protein, serum albumin, serum iron and vitamin D, serum zinc and magnesium levels were determined. A significant decrease in quality of life was proven in the group of patients with chronic pancreatitis and hypertension. Significantly lower indicators of psychological health and role functioning were noted among the 45–55-year-old group, and among patients 56–65 years had significantly lower indicators of physical functioning, role-based physical functioning, vitality and social functioning, which correlated with markers of malnutrition. The level of total protein, albumin, vitamin D, and iron in blood serum can be markers of malnutrition in patients with chronic pancreatitis combined with hypertension.